Acupuncture-moxibustion for chemotherapy-induced peripheral neuropathy: A systematic review and network meta-analysis - Yan LI; Shuang LIU; Hai-fa QIAO (World Journal of Acupuncture - Moxibustion)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common neurotoxic reaction for patients undergoing anticancer regimens. More and more studies show that acupuncture-moxibustion plays a positive role in the management and prevention of CIPN. Objective: To evaluate the clinical effect of acupuncture-moxibustion in patients with CIPN, with a focus on assessing its effectiveness on improving treatment response rates, alleviating pain, enhancing quality of life (QoL), and improving nerve conduction. Additionally, the study compares the differences in clinical effectiveness among various acupuncture therapies for CIPN management. Methods: Six databases (PubMed, Embase, Cochrane Library, Web of Science, OVID, and China National knowledge infrastructure [CNKI]) were searched from earliest available dates to December 1, 2024, and only randomized controlled trials (RCTs) containing relevant search terms were included. Network meta-analysis of the RCT data were conducted to assess the effective rate of the treatment as the primary outcome. Nerve conduction, pain scores, and QoL were assessed as secondary outcomes. The version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB 2) was used to examine methodological quality, and Stata 15.1 was used to take network meta-analysis. Results: A total of 34 RCTs involving 2039 participants and 9 acupuncture-moxibustion therapies were included. The network meta-analysis evaluated the effect of different acupuncture therapies across four outcomes: effective rate, pain scores, QoL, and nerve conduction. For effective rate, electroacupuncture combined with moxibustion ranked first with a surface under the cumulative ranking curve (SUCRA) value of 62.9 %, followed by acupoint application (56.9 %) and moxibustion (52.3 %). Electroacupuncture combined with moxibustion had the highest effective rate compared to standard of care treatments (odds ratio [OR] = 1.62, 95 % confidence interval [CI] −5.18 to 8.43). For alleviating pain, auricular acupressure had the highest SUCRA value (85.9 %), while electroacupuncture and electroacupuncture combined with three-edged needle ranked second (63.4 %) and third (51.0 %), respectively. Auricular acupressure significantly reduced pain (SMD= −1.73, 95 % CI −3.54 to 0.08). For QoL, warming needle ranked first (SUCRA= 92.0 %), followed by electroacupuncture (48.7 %) and filiform needle (43.0 %). Warming needle significantly improved QoL scores (SMD= −0.75, 95 % CI −1.66 to 0.15). For nerve conduction, electroacupuncture combined with three-edged needle had the highest SUCRA value (100 %), while moxibustion and filiform needle ranked second (65.3 %) and third (39.2 %), respectively. Electroacupuncture combined with three-edged had the best neuroprotective effect (SMD = 1.85, 95 % CI 1.23 to 2.47). Conclusion: Network meta-analysis based on the primary outcome (effective rate) suggests that electroacupuncture combined with moxibustion seems to be the optimal acupuncture therapy for chemotherapy-induced peripheral neuropathy (CIPN). Secondary outcomes exhibited considerable heterogeneity: auricular acupressure demonstrated superior efficacy in pain relief, electroacupuncture combined with three-edged needle showed greater advantages in improving nerve conduction function, while warm needling was associated with more significant improvements in QoL. Given the variability in interventions across different outcome measures and the methodological limitations of included studies, the current evidence requires cautious interpretation. Systematic review registration: Registration number in PROSPERO: CRD42024560017.